Strategy For Improving The Quality of Public Services In Permit Management in Article 4 of Law Number 25 of 2009 Concerning Public Service - Rivay Kaimudin; M. Mas’ud Said; Rulam Ahmadi (Universitas Islam Malang, 2023)
Problems arise in improving the quality of public service delivery regarding rental transport licensing at the East Seram-Maluku Regency Transportation Service, which are still hampered by a lack of human resources in providing good service, accompanied by a lack of service infrastructure so that the licensing implementation system cannot work properly. as well as a lack of supervision of public transportation activities on the highway so that it is not orderly in providing services to the community. This writing is motivated by the existence of problems, namely related to strategies to improve the quality of public services in Licensing Management at the East Seram Regency Transportation Agency, then procedures for improving the quality of public service delivery in Licensing Management at the East Seram Regency Transportation Agency, as well as the inhibiting factors for improving the quality of public service delivery and management Licensing at the East Seram Regency Transportation Department. The type of research carried out by this author is qualitative descriptive research. The data collection technique used in this study was obtained through the Library Studies and Field Studies conducted by interviews and observations. And analyzed qualitatively by combining library research and field research.